An Incident Control Centre in Action: Response to the Rena Oil Spill in New Zealand. (20th January 2014) - Hunt, Sonya; Smith, Kelly; Hamerton, Heather; Sargisson, Rebecca J.
<x xml:space="preserve">Abstract</x> Following the Rena grounding and oil spill in the Bay of Plenty, New Zealand, an Incident Command Centre was established which, among other tasks, coordinated a volunteer clean‐up effort. We interviewed volunteers and organisers to gain insight into the efficacy of the volunteer coordination effort. Volunteers praised the system of communication and the involvement of indigenous groups. They expressed a desire for better training, more flexibility and community autonomy, a quicker uptake of volunteer support, and the use of social media. Locating the Incident Command Centre in a single site aided interaction between experts, and the sharing of resources. Overall, the volunteer coordination was considered a success.